Reliability, failure probability, and strength of resin-based materials for CAD/CAM restorations (Journal of Applied Oral Science, 2016)
Objective: This study investigated the Weibull parameters and 5% fracture probability of direct, indirect composites, and CAD/CAM composites. Material and Methods: Discshaped (12 mm diameter x 1 mm thick) specimens were prepared for a direct composite [Z100 (ZO), 3M-ESPE], an indirect laboratory composite [Ceramage (CM), Shofu], and two CAD/CAM composites [Lava Ultimate (LU), 3M ESPE; Vita Enamic (VE), Vita Zahnfabrik] restorations (n=30 for each group). The specimens were polished, stored in distilled water for 24 hours at 37°C. Weibull parameters (m= modulus of Weibull, σ0= characteristic strength) and flexural strength for 5% fracture probability (σ5%) were determined using a piston-on-three-balls device at 1 MPa/s in distilled water. Statistical analysis for biaxial flexural strength analysis were performed either by both one-way ANOVA and Tukey's post hoc (α=0.05) or by Pearson's correlation test. Results: Ranking of m was: VE (19.5), LU (14.5), CM (11.7), and ZO (9.6). Ranking of σ0 (MPa) was: LU (218.1), ZO (210.4), CM (209.0), and VE (126.5). σ5% (MPa) was 177.9 for LU, 163.2 for CM, 154.7 for Z0, and 108.7 for VE. There was no significant difference in the m for ZO, CM, and LU. VE presented the highest m value and significantly higher than ZO. For σ0 and σ5%, ZO, CM, and LU were similar but higher than VE. Conclusion: The strength characteristics of CAD/ CAM composites vary according to their composition and microstructure. VE presented the lowest strength and highest Weibull modulus among the materials.